Extraction and Qualitative Analysis of Floral Volatiles of Alstonia scholaris - cruza, Kevin J. D; Ambatkar, Mugdha V (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The strong fragrance of the flowers of Alstonia scholaris indicates the presence of volatile compounds. The pharmacological properties of the flowers of A. scholaris have been explored to a lesser extent than those of the bark and leaves. In the present study, the floral volatiles were extracted by steam distillation, and the major components were identified using GC–MS analysis. The cooling system in the distillation set-up was modified to significantly reduce the wastage of water. The distillate contained terpenes, such as eucalyptol (1,8-cineole) and linalool, which have well established medicinal properties. The present study qualitatively identified those volatiles that can be extracted from the flowers by through steam distillation, without the use of an organic solvent. The study explores the potential of the flowers of A. scholaris as a source of fragrant compounds with biologically activity.